2014
DOI: 10.1530/rep-14-0027
|View full text |Cite
|
Sign up to set email alerts
|

The role of SRC1 and SRC2 in steroid-induced SDF1 expression in normal and ectopic endometrium

Abstract: To compare the expression patterns of steroid receptor coactivators (SRCs) and steroid-induced stromal cell-derived factor 1 (CXCL12 (SDF1)) in normal and ectopic endometrium and to explore the roles of NCOA1 (SRC1) and NCOA2 (SRC2) in the steroid-induced CXCL12 expression in normal and ectopic endometrial stromal cells (ESCs). The NCOA1, NCOA2, NCOA3 (SRC3), and CXCL12 (SDF1)a mRNA levels in normal and ectopic endometrium were analyzed by quantitative real-time PCR. Steroid-induced CXCL12 expression was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
6
0
3
Order By: Relevance
“…26 Estradiol stimulates CXCL12 production and progesterone to inhibit this stimulation. 27,28 In vitro, AMD3100 blocked the CXCL12-mediated proliferative effects on epithelial cells. 29 Acute treatment of experimental endometriosis in mice with AMD3100 significantly decreases lesion volume and reduces BM cell trafficking to lesions.…”
mentioning
confidence: 94%
“…26 Estradiol stimulates CXCL12 production and progesterone to inhibit this stimulation. 27,28 In vitro, AMD3100 blocked the CXCL12-mediated proliferative effects on epithelial cells. 29 Acute treatment of experimental endometriosis in mice with AMD3100 significantly decreases lesion volume and reduces BM cell trafficking to lesions.…”
mentioning
confidence: 94%
“…Endometriosis (EMS; ectopic endometrium) is an estrogen-dependent and inflammatory complex disease where immunological factors and angiogenesis play a pivotal role in its pathogenesis (Gazvani and Templeton, 2006;Rizner 2009). Shi et al showed that the expression of NCOA1 was greater in ectopic endometrium than that of normal endometrium, and NCOA1 was involved in the expression of stromal cell-derived factor 1 (SCDF1/CXCL12) whose expression was induced by estradiol (Shi et al, 2014).…”
Section: Endometriosismentioning
confidence: 99%
“…Unlike normal ESCs, progesterone did not alter increased expression of these matrix molecules in endometrioma-derived SCs. Some of this insensitivity to progesterone may be due to a number of factors including decreased PR levels, increased progesterone metabolism (Bulun et al, 2006(Bulun et al, , 2010 changes in cell-specific coactivators/repressors (Suzuki et al, 2010;Shi et al, 2014;Zelenko et al, 2012).…”
Section: Progesterone and Endometrioma Stromal Cellsmentioning
confidence: 99%